2020
DOI: 10.1111/jch.13988
|View full text |Cite
|
Sign up to set email alerts
|

Effects of luseogliflozin on arterial properties in patients with type 2 diabetes mellitus: The multicenter, exploratory LUSCAR study

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 54 publications
(52 reference statements)
1
28
0
Order By: Relevance
“…This suggests that other between‐trial differences and potential confounders could have contributed to the findings of different studies, and therefore, a class effect may still be possible. Certainly, SGLT2 inhibitors have a number of other beneficial actions that are likely to contribute to reductions in cardiovascular risk, including reductions in body weight and BP and improvement in glycemic control, 17,18 as were seen with luseogliflozin in our study 2 …”
supporting
confidence: 61%
See 1 more Smart Citation
“…This suggests that other between‐trial differences and potential confounders could have contributed to the findings of different studies, and therefore, a class effect may still be possible. Certainly, SGLT2 inhibitors have a number of other beneficial actions that are likely to contribute to reductions in cardiovascular risk, including reductions in body weight and BP and improvement in glycemic control, 17,18 as were seen with luseogliflozin in our study 2 …”
supporting
confidence: 61%
“…We appreciate the comments from Dr Patoulias and colleagues 1 regarding our study investigating the effects of the sodium‐glucose cotransporter 2 (SGLT2) inhibitor, luseogliflozin, on arterial stiffness in patients with diabetes mellitus 2 . The results of our single‐arm study did not show any favorable effect of luseogliflozin on arterial stiffness, measured using the cardio‐ankle vascular index (CAVI) 2 . As a measure of arterial stiffness, CAVI is relatively independent of blood pressure (BP) and is now widely used in cardiovascular research and clinical practice 3–7 …”
mentioning
confidence: 99%
“…On the other hand, some potential conventional risk factors for arterial stiffness such as fasting hyperglycemia or insulin resistance [31,41,42] were not included in the multivariate regression analysis. Finally, multiple anti-diabetic agents including sodiumglucose cotransporter 2 inhibitors [43][44][45][46], but not all anti-diabetic agents [47], have been shown to improve arterial stiffness. In this regard, FLP-CGM-derived metrics related to intra-day glucose variability such as SD and MAGE, and metrics related to hyperglycemia such as TAR > 13.9 mmol/L and HBGI, were still significantly associated with high arterial stiffness, even after adjusting for the use of anti-diabetic agents (Additional file 1: Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of SGLT2 inhibitors, such as tofogliflozin [ 12 ], empagliflozin [ 13 15 ], and canagliflozin [ 16 ], on arterial stiffness have been revealed in clinical studies using other indices of arterial stiffness, such as ambulatory arterial stiffness index [ 13 ], pulse pressure, mean arterial pressure, double product [ 16 ], and cardio-ankle vascular index (CAVI) [ 12 ]. However, several studies did not find beneficial effects of this class of antidiabetics on arterial stiffness [ 18 ]. Patoulias et al recently reviewed and summarized clinical studies on this topic and concluded that evidence on the effect of SGLT2 inhibitors on arterial stiffness remains limited and controversial [ 19 ].…”
Section: Discussionmentioning
confidence: 99%